Transformasi Digital Dalam Pelayanan Publik: Peran Kearsipan Elektronik di Biro Umum Gubernur Sumatera Utara - Wahyuni Khalida; M.Ridwan (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
. Digital transformation has emerged as the primary driver in modernizing public services, altering the way governments interact with citizens. A key component of this transformation is the implementation of electronic archiving, enabling more efficient and structured information management. This research aims to examine the vital role of electronic archiving in strengthening digital transformation in public services, with a specific focus on the General Bureau of the North Sumatra Governor's Office. The research methodology employed is a qualitative approach, with a case study analysis of the General Bureau of the North Sumatra Governor's Office as the main focal point. Data was gathered through in-depth interviews, observations, and analysis of relevant documents. The research findings indicate that electronic archiving has significantly contributed to accelerating information access and enhancing the efficiency of public service processes within this institution. These findings offer recommendations for enhancing the implementation of electronic archiving in the General Bureau of the North Sumatra Governor's Office, while also contributing to a deeper understanding of the pivotal role of electronic archiving in the era of digital transformation in public services.